Macroeconomic Determinants of Global Islamic Bank Profitability: The Moderating Role of Non-Performing Financing - Nidaul Husnia; Eka Wahyu Hestya Budianto (JURNAL ECONOMINA, 2026)
This study explores how macroeconomic factors, namely inflation, interest rates, exchange rates, GDP growth, and unemployment rates, influence the profitability of global Islamic banks, with Return on Assets (ROA) serving as the profitability indicator. In addition, the study evaluates whether Non-Performing Financing (NPF) plays a moderating role in the relationship between these macroeconomic variables and bank profitability. The analysis is based on secondary data collected from the World Bank, the International Monetary Fund (IMF), and the annual reports of 58 Islamic banks operating across different countries during 2020-2025. Using panel data regression and Moderated Regression Analysis (MRA), the Random Effect Model (REM) was identified as the most appropriate estimation approach. The findings show that inflation, exchange rates, and GDP growth contribute positively to ROA, whereas interest rates have a significant negative effect. On the other hand, unemployment rates and NPF do not demonstrate a significant influence on profitability. The moderation results further reveal that NPF only affects the relationship between exchange rates and ROA, while its moderating role is not evident for inflation, interest rates, GDP growth, or unemployment rates. Collectively, the variables examined in this study are found to significantly explain the profitability of global Islamic banks.